Imperfection sensitivity of shear banding in gradient-dependent Cam-clay plasticity model - Stankiewicz, Anna (Computer Assisted Methods in Engineering and Science, 2015)
The paper deals with the numerical simulation of strain localization in granular two-phase material. A gradient enhancement of modified Cam-clay model is introduced to overcome the problem of spurious discretization sensitivity of finite element solution. Two- and three-field finite elements implemented in the finite element analysis program (FEAP) are used in numerical simulations. The attention is focused on imperfection sensitivity of shear banding simulations. An application of the modelling framework to the slope stability problem is also included.